Story Analysis in Documentary “The Waste On The Hills” - Kabelen, Nicholaus Wayong (Universitas Ciputra, 2023)
The purpose of this research is to analyze the story of the daily routine of TPA Piyungan Yogyakarta in the documentary film The Waste On The Hills by Himawan Pratista. Social and environmental problems are clearly visible, where this TPA has actually exceeded its capacity. piyungan landfill has been operation since 1995, and it has to be stopped using in 2016, but until now, it still in use the height of the garbage dump from the ground has reached more than a 20 fibors building. Low public awareness in environmental management can be a cause of environmental pollution. Then efforts to manage waste that are not effective will result in health problems for humans and livestock around the landfill. In the middle of the pile of garbage there are lots of scavengers looking for trash to sell again. The results of writing this article aim to analyze and describe or explain the factors that cause and impact caused by piles of garbage. The writing of this article also uses a qualitative descriptive approach method opinion raising starting from 01:00 to 06:00 then the climax begins to appear at 09:15 on 3 quarters of the duration of the film.